PENGARUH MODEL THINK PAIR SHARE TERHADAP HASIL BELAJAR SISWA SMA TAMAN MULIA KUBU RAYA - Indrawati Indrawati; Budiman Tampubolon; Agus Sugiarto (Universitas Tanjungpura, 2020)
AbstractThe purpose of this is toknow the implementation of comperative model of think pair share type toward geography lesson in the result of students study in grade X IIS Senior high School Taman Mulia Kubu Raya. The research method the used in the experiment in the Quasi Experiment Design model. The population in all of grades of X IIS, the sample of this research is grade X IIS 2 and grade X IIS 1. The technique of data collection is using the measurement technique and data collection tools is written test. In the research results obtained the average of final test in control class is 75,889 and the average of final test in experiment class is 79,857. The result of t-test obtained t-count is 3,282 and t-table (α =5% with dk= 53) is 2,0073, meaning t count ( 3,282)> t table ( 2,0073), thus Ha is accepted. The effect size calculation, obtained is 0,98 (high category).Thersore, it could be conclude that there is influence to the cooperative model of think pair share type towards the results of study results of student in grade X IIS Senior High School Taman Mulia Kubu Raya.Kyword: learning Outcomes, Think Pair Share